2011
DOI: 10.1007/s13157-011-0147-x
|View full text |Cite
|
Sign up to set email alerts
|

Water Sources and Hydrodynamics of Closed-Basin Depressions, Cook Inlet Region, Alaska

Abstract: Among the most prevalent wetland and deepwater habitats in Alaska are ponds, many of which are subarctic ponds occurring as moraine, ice-scour, or dead-ice depressions. Many are closed-basin depressions, where surface-water inflows and outflows are negligible. The objective of this study was to quantify the water sources and hydrodynamics of these subarctic ponds, particularly with respect to the role they play in groundwater recharge. There are two types of ponds on the study site. Perchedprecipitation ponds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Moreover, as noted, wetlands can be focal points for groundwater recharge, which may contribute to baseflow. Rains (), for example, found that perched and flow‐through wetland ponds in southwestern Alaska were sites of net groundwater recharge. Given the high prevalence of ponds on the landscape (Rains ), these wetlands could substantially affect stream baseflow via groundwater inputs (see Groundwater Connectivity below).…”
Section: Hydrological Physical and Chemical Functions Of Nfwsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as noted, wetlands can be focal points for groundwater recharge, which may contribute to baseflow. Rains (), for example, found that perched and flow‐through wetland ponds in southwestern Alaska were sites of net groundwater recharge. Given the high prevalence of ponds on the landscape (Rains ), these wetlands could substantially affect stream baseflow via groundwater inputs (see Groundwater Connectivity below).…”
Section: Hydrological Physical and Chemical Functions Of Nfwsmentioning
confidence: 99%
“…), NFWs in glacially formed landscapes in southwest Michigan (Kehew et al. ), Alaskan pond NFWs (Rains ), Florida cypress dome NFW systems (Sun et al. ), and small Wisconsin lakes (Born et al.…”
Section: Hydrological Physical and Chemical Functions Of Nfwsmentioning
confidence: 99%
“…) and supplying baseflow (Morley et al. ; Rains ). Despite the acknowledged role of wetlands in the hydrologic resilience of watersheds, there has been a rapid global decline in wetland area, with an average estimated global loss of wetland area since 1970 of 31% (Dixon et al.…”
Section: Introductionmentioning
confidence: 99%
“…Small water bodies were located relatively higher in the landscape than larger water bodies ( Fig. 5; Table 3) and so may be recharged less frequently by either surface or subsurface flows even as annual precipitation increases (Rains 2011). Similarly, water bodies located higher in the landscape may be less likely to be connected to drainage inlets.…”
Section: Water Bodiesmentioning
confidence: 99%